2016
DOI: 10.1016/j.archger.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Health, frailty and disability after ninety: Results of an observational study in France

Abstract: This study shows the diversity of health states in very old age and points out that one quarter of the people aged 90 and over said frail are likely to take advantage of preventive actions of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 54 publications
2
35
0
3
Order By: Relevance
“…The results of the 5-COOP study confirm that frailty involves a majority of centenarians in a much larger sample and are in line with the above-mentioned studies [9,15,20,24]. This very high prevalence of frailty in centenarians raises the question of whether an additional category corresponding to people having 4-5 frailty criteria should be distinguished in order to discriminate "very frail" or "super-frail" people from frail people (still not dependent in ≥2 ADL for 25% of them).…”
Section: Prevalence and Characteristics Of Frailtysupporting
confidence: 77%
See 2 more Smart Citations
“…The results of the 5-COOP study confirm that frailty involves a majority of centenarians in a much larger sample and are in line with the above-mentioned studies [9,15,20,24]. This very high prevalence of frailty in centenarians raises the question of whether an additional category corresponding to people having 4-5 frailty criteria should be distinguished in order to discriminate "very frail" or "super-frail" people from frail people (still not dependent in ≥2 ADL for 25% of them).…”
Section: Prevalence and Characteristics Of Frailtysupporting
confidence: 77%
“…A meta-analysis of Japanese studies estimated the prevalence of frailty at 35% among 407 community-dwelling people aged 85 years and over [24]. A French study among 512 nonagenarians reported that 54% of the participants met the criteria for frailty, in the absence of disability in half of them [9]. In 2014, a Portuguese study estimated the prevalence of frailty at 60% in a sample of 50 centenarians [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging Clinical and Experimental Research should also consider to publish more work on the role of environmental factors because the revolution of adult longevity is leading to an accumulation of very old people presenting an increased vulnerability to environmental stresses [8]. For all these reasons, gerontology journals should play a central role in the publication of work on the effect that environmental factors can have on health.…”
Section: In This Issue Aging Clinical and Experimental Researchmentioning
confidence: 99%
“…The number of oldest-old people aged >90 has been growing in Italy in the last decades (Bonarini 2009). In spite of their increasing demographic weight, the health characteristics of the oldest old remain poorly described in epidemiological studies (Herr et al 2016).…”
Section: Introductionmentioning
confidence: 99%